Food and agriculture systems foresight study: Implications for gender, poverty, and nutrition - Lentz, Erin C. (Oxford University Press, 2021)
This review evaluates foresight studies to understand how the future agri-food system may impact gender, poverty, and nutrition (GPN). Foresight studies agree that it will be challenging to transform the agri-food system into one that is sustainable, healthy, and just, although the degree to which foresight studies consider GPN is uneven. Foresight work with a GPN focus tends to assume that global coordination of policies and regulations is both necessary and possible in order to achieve improved GPN outcomes. However, history has shown that efforts to coordinate globally are mixed. At the same time, innovation-led studies pay less attention to barriers to equitable adoption and nutritional outcomes. Yet, the history of development has demonstrated the difficulties of equitable implementation of and access to new technological innovations, particularly for women and marginalized populations. I argue that mainstreaming GPN into foresight research can inform both policy-led and innovation-led pathways that support an improved agri-food system. The use of multisectoral and multilevel tools and analyses can support future foresight research and policymaking to systematically identify the net influences on and trade-offs among GPN and other factors.